Pengaruh Makanan terhadap Produktivitas Pekerja PT. Niramas Utama - Auliya Ulfa (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to understand how food affects employee productivity at PT. Niramas Utama. The methodology used is qualitative by conducting in-depth interviews and direct observations related to employee eating patterns and work attitudes. The findings of the study indicate that a good and regular diet, especially a nutritious breakfast, has a positive impact on employee energy, focus, and daily performance. On the other hand, irregular eating patterns and fast food consumption have a negative effect on employee productivity and well-being. The SWOT analysis reveals that the company has the opportunity to increase productivity by changing food provision policies and providing educational support on nutrition. The suggestions from this study emphasize the importance of the company's attention to nutritional aspects related to work as part of a strategy to improve employee performance and well-being.